ANALISIS PENGARUH KUALITAS PRODUK KERANJANG TERHADAP KEPUASAN PELANGGAN PADA PURREBRA DI PECEREN BERASTAGI - Benni Purba; Menanti Sembiring; Ingan Ukur Sitepu; Piman Bastanta Barus; Edo Rivaldy (JURNAL AGROTEKNOSAINS, 2022)
This study aims to determine and analyze the effect of product quality on customer satisfaction at PURREBRA Peceren Berastagi. The study used a descriptive approach. The population in this study are all customers of the PURREBRA Peceren Berastagi basket.  The number of research samples taken as many as 100 people, with the Accidental Sampling approach, which is a sampling technique based on chance, namely anyone who happens to buy a basket if it is deemed suitable as a sample. Analysis of the data used is descriptive analysis and linear regression analysis. Data were collected by questionnaire. The results showed that: product quality has a significant effect on customer satisfaction PURREBRA Peceren Berastagi where the value of t = 6.556 with sig. 0.000 > t table = 1.666. The regression equation Y= 10,410 + 0,636X + e. R Square value of 0.305 means 30.50% and the remaining 69.50% is influenced by other factors not examined in this study.